An Analysis of the Impact of Economic Growth, The Energy Trilemma, Financial Sector Development, and Urbanization on Renewable Energy Consumption in G20 Countries - Fani Leksana; Unggul Heriqbaldi (Journal Research of Social Science, Economics, and Management, 2026)
Renewable energy consumption has become a strategic concern for G20 countries, as their energy policies strongly influence global climate mitigation, energy security, and sustainable development. This study aims to analyze the effects of economic growth, the energy trilemma index, financial sector development, and urbanization on renewable energy consumption in G20 countries. The research employed a quantitative approach using balanced panel data from 18 G20 member countries over the period 2000–2021, yielding 396 observations. Data were obtained from the World Bank World Development Indicators and the World Energy Council Trilemma Index. The analytical method used panel regression, encompassing stationarity tests, cointegration tests, classical assumption tests, the Fixed Effect Model, the Random Effect Model, and the Hausman test, which selected the Fixed Effect Model as the most appropriate estimation model. The results show that economic growth has a significant positive effect on renewable energy consumption, supporting the Environmental Kuznets Curve perspective. The energy trilemma index also has a significant positive effect, indicating that energy security, equity, and environmental sustainability encourage renewable energy adoption. Financial sector development, however, has no significant aggregate effect, while urbanization has a significant negative effect, particularly in the developing country group. This study concludes that differentiated energy policies are needed to strengthen renewable energy transitions across G20 countries.